MITOS CERITA RAKYAT NEGERI DEWI PADI DI KELURAHAN TAUBONTO KECAMATAN RAROWATU KABUPATEN BOMBANA - Hakim Hakim; La Ino (Program Studi Sastra Indonesia Fakultas Ilmu Budaya Universitas Halu Oleo, 2018)
Issues examined in this study, namely; (1) How is the structure of the State Folklore Myths goddess of rice (goddess of rice) in Sub Taubonto District of Rarowatu Bombana, (2) What is the function of myth State Folklore Goddess of Rice (goddess of rice) in Sub Taubonto District of Rarowatu Bombana. The purpose of this study, namely; (1) describe the structure of the State Folklore Myths goddess of rice (goddess of rice) in Sub Taubonto District of Rarowatu Bombana, (2) describes the functions of the State Folklore Myths goddess of rice (goddess of rice) in Sub Taubonto District of Rarowatu Bombana. The benefits of this research, namely; (1) This research can be a source of insight into the science for researchers hereinafter, (2) can be a reference for further research. The results of this study indicate that: (1) the structure of mythical folklore of State Rice Goddess (goddess of rice) version of Mr. Ndasi studied in theory structuralism Levi-Strauss found some opposition figures who build, which is the Goddess of Rice, Tangkume, Society, Tengu, and Ubi Talas, while the version Mr. Dadi Sangi, the opposition leaders who build, the Goddess of Rice and Tangkume which begins by making units of the narrative and is divided into several episodes to find differences and similarities ceriteme and also to find opposition. Units narrative of Mr. Ndasi version and the version of Mr. Dadi Sangi reconstructed into one that produced 18 units of narrative, (2) the function of mythical folklore of State Rice Goddess (goddess of rice) were studied by using the theory of functions of Van Paursen divided; (a) has miraculous powers that can be demonstrated in the following narrative unit; 5, 13, 14, 19 and 20 (b) provides jaminana today that can be demonstrated in the following narrative unit; 11, 12 and 15 (c) provides knowledge about the world that can be proved in the following narrative unit; 14, 15, 16 and 20. Keywords: Myth, Structure and Function of State Rice Goddess Folklore (goddess of rice)